Declarative and Interrogative Sentences in The Film “American Sniper” - Agung Tribawa, I Gusti Ngurah (Humanis; Vol 22 No 4 (2018), 2018)
This paper entitled “Declarative and Interrogative Sentences in the Film “American Sniper” is mainly aimed to identify the kinds and functions of declarative and interrogative sentences used in this film directed by Clint Eastwood. The data of this study is declarative and interrogative sentences taken from film entitled American Sniper . This study was using qualitative and documentary methods. The data were analyzed qualitatively in accordance with some related theories to define the kinds and functions of declarative and interrogative sentences. The theories used in this study are declarative sentence theory “ Declarative sentence is a sentence that used to expressing of the statement, it completely formed sentence elements such a subject, verb, object, and another element. ” by Quirk (1985) and interrogative sentence theory “ Interrogative is a term used in grammar to refer to features that form questions. ” by John Eastwood (1994). Then the data were presented descriptively by explaining the process and the result of discussion. The finding in the analysis shows that declarative and interrogative sentences was used in the film American Sniper. The result is: two kinds of declarative sentences, positive and negative declarative sentence, and eight kinds of interrogative sentences: (a) yes-no question; (b) w-h question; (c) suggestion; (d) command; (e) request; (f) greeting; (g) confirmation; (h) offering.